مقارنة الوظيفية و الإجهادية بين قميص وتر الرضفة و قميص الالتصاق الكامل - نجار, رائد; محمد, يارا; علي, غدير (Latakia University Journal -Engineering Sciences Series, 2019)
The aim of this research is to study and evaluate the efficiency of two types of sockets used in the case of amputation below the knee, PTB socket and full contact socket through the computer modeling of each one based on the CT image and finite element analysis through 3D design and analysis programs and results approach through clinical follow-up after manufacturing both sockets and using them for a week on amputation below the knee. A 46-year-old male with free scars and subcutaneous amputation. The results were discussed in terms of comfort, efficiency and side-effects. The analysis was based on stress values in both sockets and compared with the results of clinical trials, the maximum value In the PTB were in patellar tendon area in the Full Contact sockets were in the lower region due to the absence of the suspension system and the areas of the patellar tendon, but at the same time caused a sense of muscle convulsions. يهدف هذا البحث إلى دراسة و تقييم كفاءة نوعين من أهم القمصان المستخدمة في حالة البتر من ما تحت الركبة و هما قميص وتر الرضفة PTB و قميص الالتصاق الكامل Full Contact من خلال النمذجة الحاسوبية لكل قميص اعتماداَ على صورة الطبقي المحوري CT و التحليل بالعناصر المنتهية FEA من خلال برامج التصميم و التحليل ثلاثي الأبعاد و مقاربة النتائج من خلال المتابعة السريرية بعد تصنيع كلا القميصين و استخدامهما لمدة أسبوع على مصاب بالبتر من ما تحت الركبة ذكر عمره 46 عاماً و و يمتاز ببتر خالٍ من الندبات و الشظايا تحت الجلد و مناقشة النتائج من حيث الراحة و الكفاءة و المضاعفات الجانبية, تم الوصول من خلال التحليل إلى قيم الإجهادات الناظمية في كلا القميصين و مقارنتها مع نتائج الاختبارات السريرية حيث بلغت قيمة الإجهادات ذروتها في قميص PTB في منطقة وتر الرضفة و بلغت قيمتها العظمى في قميص الالتصاق الكامل في المنطقة السفلية منه و ذلك لعدم وجود نظام التعليق و مناطق الاستناد على وتر الرضفة و لكنه سبب في نفس الوقت احساساً بقوة السحب و الاختلاجات العضلية .